INTERNET, MULTIMEDIA AND THE EFFORT PUT INTO LEARNING ENGLISH LANGUAGE - Sunčana Tuksar; Moira Kostić Bobanović (Hum, 2020)
In the present globally networked society English language is lingua franca especially promoted by internet. In face-to-face teaching, and especially online teaching, media transfer information, language and culture, and therefore multimedia, or multimodal communication stands out as necessary for stimulating critical visual literacy and learning English language. That is the way it is because correlation of image and text intermediates in the manner which strengthens the individual’s self-awareness of language and culture knowledge and activates his efforts and engagement in learning. Taking into consideration the above mentioned, this paper seeks to examine the following: a) the effort put into learning English language and b) ratio of the effort put into face-to-face and online teaching. The survey was conducted at the Juraj Dobrila University of Pula during the academic year 2019/2020, period of the obligatory staying at home because of Coronavirus pandemic. Such and similar research will be in the future important for permeation of media represented information as well as for expansion or replacement of face-to-face teaching in usual communication circumstances or in the circumstances when online teaching is the only option